PENGEMBANGAN SECARA SPASIAL BENTENG OTANAHA DI KAWASAN CAGAR BUDAYA GORONTALO - Dwi Randayani Butulipu; Ivan Taslim; Ahmad Syamsu Rijal (Universitas Muhammadiyah Gorontalo, 2018)
Abstract – This study aims to analyze the development of tourist areas of Benteng Otanaha spatially by using SWOT and GIS analysis. Data obtained in the form of primary data include field observation, interviews, questionnaires, field documentation and secondary data in the form of data collection through document studies and literature study. The results of this study indicate that tourism in Benteng Otanaha in the cultural heritage area has good potential to be developed because it includes cultural preservation based on diversity, uniqueness and distinctiveness of culture and nature as well as human needs for a vacation. The development of Otanaha Fortress in the cultural heritage area requires follow up of local government and community, so it can be one of the tourist destinations in Gorontalo. Keywords: spatial development, swot analysis, gis, otanaha castle, cultural heritage, gorontalo Abstrak – Penelitian ini bertujuan untuk menganalisis pengembangan kawasan wisata Benteng Otanaha secara spasial dengan menggunakan analisis SWOT dan SIG. Data yang diperoleh berupa data primer meliputi observasi lapangan, wawancara, kuesioner, dokumentasi lapangan dan data sekunder berupa pengambilan data melalui studi dokumen dan studi pustaka. Hasil penelitian ini menunjukkan bahwa pariwisata di Benteng Otanaha di kawasan cagar budaya memiliki potensi yang sangat baik untuk dikembangkan karena meliputi pelestarian budaya berdasarkan keragaman, keunikan dan kekhasan budaya dan alam juga kebutuhan manusia untuk berlibur. Pengembangan Benteng Otanaha di kawasan cagar budaya memerlukan tindak lanjut dari pemerintah daerah dan masyarakat, sehingga dapat menjadi salah satu tujuan wisata di Gorontalo. Kata Kunci: pengembangan spasial, analisis swot, sig, benteng otanaha, cagar budaya, gorontalo